A COMPARATIVE STUDY OF SPATIAL POLICY IN INDONESIA AND THE NETHERLANDS - Haris Budiman; Anis Mashdurohatun; Eman Suparman (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Spatial planning policy in Indonesia is not effectively implemented due to land conversions and other problems. This occurs since the spatial planning policy is sectoral especially since the enactment of regional autonomy. This research accordingly tries to explain how the management of spatial policy in Indonesia compared to the Netherlands. The method used was juridical normative. The results of the research showed that in its implementation of spatial policy in Indonesia, regional governments have the authority to make their own policy. Nevertheless, the spatial policy in the Netherlands is based on efforts to improve and secure accessible space with the first priority on users. Therefore, although the spatial policy is based on the community participation, the control remains on the Central Government’s hand. In conclusion, it takes comprehensive measures and social participation to formulate spatial policy. Keywords: comparative law, policy, spatial planning